2014
DOI: 10.1088/1009-0630/16/1/12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Plasma Treatment on Seed Germination and Growth of Wheat

Abstract: This study investigated the effect of cold helium plasma treatment on seed germination, growth and yield of wheat. The effects of different power of cold plasma on the germination of treated wheat seeds were studied. We found that the treatment of 80 W could significantly improve seed germination potential (6.0%) and germination rate (6.7%) compared to the control group. Field experiments were carried out for wheat seeds treated with 80 W cold plasma. Compared with the control, plant height (20.3%), root lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
158
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(172 citation statements)
references
References 21 publications
13
158
1
Order By: Relevance
“…(2003) indicated a high correlation between stomatal conductance and photosynthesis rate per unit leaf area 26 . Using cold helium plasma at the booting stage, it was observed that the treated wheat had more length and stronger roots as the key factors to increase absorption of water and nutrition 27 . Due to plasma treatment the plant height is increased and as the result the plant could compete for more sunlight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2003) indicated a high correlation between stomatal conductance and photosynthesis rate per unit leaf area 26 . Using cold helium plasma at the booting stage, it was observed that the treated wheat had more length and stronger roots as the key factors to increase absorption of water and nutrition 27 . Due to plasma treatment the plant height is increased and as the result the plant could compete for more sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Due to plasma treatment the plant height is increased and as the result the plant could compete for more sunlight. Higher level of absorption of PAR (photosynthetically active radiation) causes higher stomatal conductance, leaf area and chlorophyll content 27 . On the other hand the absorption level of PAR causes osmolite accumulation such as soluble sugars and carbohydrates 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma is formed by a discharge in a gas, and in the case of an air plasma consists of ions, energetic electrons, neutral species, reactive oxygen species (ROS) and reactive nitrogen species (RNS) and produces electromagnetic radiation such as UV. Preliminary investigations have confirmed that plasma pre-treatment of seeds of important agricultural crops is an effective tool for improvement of germination, shoot, and root growth 10,11 . The plasma treatments provide good fungicidal and bactericidal effects, and increased water permeability through surface coat etching and stimulation of germination and seedlings growth 1116 .…”
Section: Introductionmentioning
confidence: 94%
“…3,4,37,38 The improved germination by plasma discharge on the seed surface can be correlated to several factors such as increase in surface wettability, 14 killing of bacteria and pathogens on the seed surface. 20,21 In addition, the local heating probably opens up the seed coating and increases the water intake.…”
mentioning
confidence: 99%